1978
DOI: 10.1207/s15327752jpa4203_10
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Self-Consciousness

Abstract: Examined the relationship between the three subscales of the Self-Consciousness Scale and a variety of other personality dimensions, including measures of reflectivity, self-regulation, and social desirability. Data from six geographically diverse samples (total N = 1395) were presented. In general, both the construct validity and discriminant validity of the subscales were supported. First, private self-consciousness significantly correlated with the Guilford-Zimmerman Thoughtfulness Scale and the Paivio Imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
1
4

Year Published

1979
1979
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(80 citation statements)
references
References 10 publications
4
71
1
4
Order By: Relevance
“…Participants respond to how representative the statements are of themselves on a 5-point rating scale ranging from 0 (not at all like me) to 4 (extremely characteristic or true of me). The scale has been shown to have good reliability and validity (e.g., Carver & Glass, 1976;Fenigstein, et al 1975;Turner, Scheier, Carver, & Ickes, 1978).…”
Section: Symptomatologymentioning
confidence: 99%
“…Participants respond to how representative the statements are of themselves on a 5-point rating scale ranging from 0 (not at all like me) to 4 (extremely characteristic or true of me). The scale has been shown to have good reliability and validity (e.g., Carver & Glass, 1976;Fenigstein, et al 1975;Turner, Scheier, Carver, & Ickes, 1978).…”
Section: Symptomatologymentioning
confidence: 99%
“…In testing this theory, Pryor, Gibbons, Wicklund, Fazio, and Hood (1977) thus found that the correspondence between self-ratings of sociability and actual social behavior was increased when subjects' degree of concurrent self-focus was enhanced by the presence of a mirror. From an individual-differences perspective, Scheier, Buss, and Buss (1978) and Turner, Scheier, Carver, and Ickes (1978) reported higher correlations between self-reports and behavior among subjects who were high rather than low in their dispositional levels of self-consciousness. Indeed, Carver and Scheier (1981) argued that as a general rule, focusing attention on the self produces more valid reports about mental states.…”
mentioning
confidence: 94%
“…In fact. Cheek and Melchior (1990) present evidence that measures of shyness and self-esteem are substantially inversely correlated (i.e., typically r = -.50), while public self-consciousness shows less covariation with self-esteem (e.g., r = -.26; Tumer, Carver, Scheier, & Ickes, 1978). Given this distinction, it would be expected that public self-consciousness should covary with cognitive and behavioral responses that reflect a cautious approach to social interaction but not with responses that reflect self-derogatory ideation.…”
mentioning
confidence: 94%